Control Self Assessment (CSA) In Improving Company Performance - Vicky Harahap; Novita Novita (Jurnal Akuntansi, Keuangan, dan Manajemen, 2022)
Purpose: This study aims to determine the effect of the internal control system using control self assessment in improving the company’s financial and non-financial performance. Method: This study uses descriptive analysis and verification analysis with partial least square, the sampling technique used in this study is a saturated samping technique where all members of the population are used as samples, which are 45 employees at the D’Specialist consultant company. Result: Control self assessment can improve company performance which is represented by financial customer, intercal process, growth and learning perspectives by implementing environmental control, risk identification, activity control, supervision, and information and communication. Limitation: The limitation in this study is in the use of research tools which are only in the form of questionnaires and online interviews because the research period was carried out during the COVID-19 pandemic large scale social restriction so that many employees worked from home. Contribution: Implementation of CSA, D'Specialist Consultant can make efforts to improve the internal control system that is able to minimize business risks and improve the company's operational and financial performance. By evaluating the internal control system regularly and thoroughly.Keywords: Control Self Assessment (CSA), Kinerja Perusahaan, Balanced Scorecard (BSC), Pengendalian internal, Risiko.